Android-Based 3D Visualization of Indonesia Medicinal Plants - Lita Karlitasari; Ismanto Ismanto; Agung Prajuhana Putra (Institute of Advanced Engineering and Science, 2017)
3D visualization of medicinal plants is the result of the transformation that resembles the original image and are dynamic, so it can be viewed in detail from all sides. Image capture is performed with a level of clarity must be at least 70% so it would be easy when designing a 3D visualization. The medicinal plants collected came from Bogor Botanical Gardens of 11 plants, Ciapus - Bogor of 16 plants, and Cibodas Botanical Gardens of 37 plants. The image capture was done by using the comparison scale of human height, stem, flowers, fruits, and leaves both look forward and backward. Application development was done through the objects collection, object segmentation, object texture creation and 3D object creation. The application of 3D visualization medicinal plants can be enlarged and reduced, and rotated well to the right, left, up, and down. The medicinal plants that appears in the application was in Indonesian and Latin names, taxon and the descriptions. Therefore the general public, students, and researchers can utilize the plant objects much better.